The Existence of Pareto-Superior Price Limits - Kodres, Laura E.; O'Brien, Daniel P. (American Economic Review, 1994)
This paper examines the welfare effects of futures price limits under a simple form of market incompleteness. When prices become volatile, shocks to liquidity and fundamentals may occur between the time investors decide to trade and the time their orders are executed. This gives rise to implementation risk that cannot be transferred with contingent claims. We show that price limits partially insure implementation risk. When price fluctuations are driven by news about fundamentals, judiciously chosen price limits can be (ex ante) Pareto superior to unconstrained trade. When liquidity shocks are large, price limits benefit hedgers but harm some speculators.